2017
DOI: 10.1088/1757-899x/201/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Study of stinging nettle (urtica dioica l.) Fibers reinforced green composite materials : a review

Abstract: Abstract. Stinging Nettle (Urtica dioica L., latin) is a wild plant that grows in Indonesia, Asia, and Europe. Nettle in Bali, Indonesia is called as Lateng, Jelatang. Nettle plant has a very strong fiber and high fixed carbon. Nettle plants are covered with fine hairs, especially in the leaves and stems. When it is touched, it will release chemicals, sting and trigger inflammation that causes redness, itching, bumps and irritation to the skin. Nettle plants grow in the wild, regarded as a weed in the agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The authors showed a cellulose content of 85.93%, 6.8% hemicellulose, and 5.49% lignin. Agus Suryewan et al used various pretreatment methods for the stinging nettle and obtained (in the best case studied) 85% of cellulose, 6% of hemicellulose, and 3% of lignin using water retting and decortication 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed a cellulose content of 85.93%, 6.8% hemicellulose, and 5.49% lignin. Agus Suryewan et al used various pretreatment methods for the stinging nettle and obtained (in the best case studied) 85% of cellulose, 6% of hemicellulose, and 3% of lignin using water retting and decortication 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Bioethanol source might be considered significant because of its use as a potential, competitive with miscanthus in cellulose occurrence. Nettle can be used to produce high-quality agricultural raw materials for composites, medicine/pharmacy, textile, and energy sectors 20 22 . What is most important, stinging nettle stems always remains a waste, therefore the use of these parts of nettle for energy purposes doesn't involve the cultivation of stinging nettle intentionally for bioethanol production.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most interesting secondary metabolites found in nettle, it is worth mentioning lignans [ 39 , 40 ], as well as phytosterols and pentacyclic triterpenes, such as β-amyrin and oleanolic acid [ 41 ]. Additionally, the cortex of nettle stems contains silky and strong bast fibers valued by the biocomposite sector because of their lightweight properties and low C footprint [ 42 ]. The aim of the work carried out here is to develop a protein purification protocol so as to define the partitioning of the proteins in different cell compartments and to analyze how SuSy can display different patterns of phosphorylation in relation to different cell compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Nettles are used in traditional medicine and the food industry [ 38 ]. The analysis of the literature shows that attempts were made to create biocomposites reinforced with common nettle [ 39 , 40 , 41 ] as well as a modification to improve compatibility between hydrophilic natural fiber and hydrophobic polymer matrix in the form of chemical treatment with NaOH [ 42 ].…”
Section: Introductionmentioning
confidence: 99%